The Effect of Bilateral Orchiectomy on Total Prostate Specific Antigen (TPSA) Levels in Prostate Adenocarcinoma Patients - Sp.U, WIKAN KURNIAWAN (Academic Hospital Journal, 2024)
AbstractBackground: Hormonal therapy is one treatment option for prostate cancer. There are two main categories of hormone therapy: surgical therapy and non-surgical therapy.  Orchiectomy is the surgical method of hormone therapy; medication supplementation is the non-surgical method. Many kinds of indicators are used to track the advancement of patients with prostate cancer receiving hormone therapy. tPSA levels are one of the markers that are regularly evaluated.Methods: In this retrospective study, PSA levels in patients with prostate adenocarcinoma cancer were evaluated before and after bilateral orchiectomy.  Use the search terms "prostate cancer" and "orchiectomy" to find research subject data in the UGM Academic Hospital's medical records installation between 2020 and 2023. The study's findings will be shown in a graphic and statistical analysis while protecting the subjects' anonymity.Results: Most of the participants (n=18, 60.0%) have pre-orchiectomy tPSA level of more than 30 ng/mL, while only almost a quarter (n=7, 23.3%) of participants have post-orchiectomy tPSA level of more than 30 ng/mL. The two research groups (p<0.0001) before and after the orchiectomy procedure, significantly differ between the two research groups based on Wilcoxon paired sample test analysis.Conclusion: TPSA levels are considerably decreased by bilateral orchiectomy.